Prevalence of Common Mental Disorder and Its Association with Khat Chewing among Ethiopian College Students: A Systematic Review and Meta-Analysis - Birhanie Mekuriaw (Psychiatry Journal, 2020)
Background. Mental disorder is a global burden that affects all groups of people. Young people, particularly college/university students, are more vulnerable to common mental disorders than the general population. Thus, students may use khat to gain immediate relief from their psychological distress which may worsen again after longer time of chewing. In Ethiopia, there are studies showing discrepant and inconsistent results of common mental disorder among college/university students. Therefore, this review sought to determine the prevalence of common mental disorder and its association with khat chewing among Ethiopian college/university students. Methods. Different kinds of literature were searched from the databases of Google Scholar, PubMed/Medline, ScienceDirect, and PsycINFO. A total of 10 primary studies which report the prevalence of common mental disorder among Ethiopian college/university students were included in the review. The data were extracted using a standardized data extraction format prepared in Microsoft Excel. STATA version 14 statistical software was used for analysis. Cochran’s Q test statistics and I2 test were used to assess heterogeneity. A random effects meta-analysis model was used to estimate the pooled prevalence of common mental disorder due to the variability of the studies. Lastly, the association between common mental disorder and khat chewing was conducted. Results. The pooled prevalence of common mental disorder among Ethiopian college/university students was 37.73% (95% CI: 30.43, 45.03). The subgroup analysis showed the highest [51.9% (95% CI: 30.19, 73.70)] and lowest [33.28% (95% CI: 19.95, 46.60)] prevalences of common mental disorder among Ethiopian college/university students found in Amhara and South Nation Nationality and People regions, respectively. The pooled effect (odds ratio) of khat chewing on common mental disorder was 2.01 (95% CI: 1.38, 2.95). Conclusions. In our review, it is found that more than one-third of college/university students suffered from common mental disorder. Khat chewers were found to be twofolds more vulnerable to develop common mental disorder than nonchewers.